Cannabinoid Modulation of Excitability and Short-Term Neuronal Dynamics in the Dorsal and Ventral Hippocampus - Giota Tsotsokou; Ioanna-Maria Sotiropoulou; Klearchos Stampolitis; George D. Oikonomou; Aikaterini-Paraskevi Avdi; Costas Papatheodoropoulos (Biology, 2025)
Endocannabinoids, acting primarily through CB1 receptors, are critical modulators of neuronal activity, influencing cognitive functions and emotional processing. CB1 receptors are highly expressed in the hippocampus, primarily on GABAergic interneurons, modulating the excitation/inhibition balance. Previous evidence suggests the functional heterogeneity of CB1 receptors along the dorsoventral axis of the hippocampus. However, it is not known whether CB1 receptors differentially modulate basic aspects of the local neuronal network along the hippocampus. This study investigated how CB1 receptor activation modulates excitability, paired-pulse inhibition (PPI), and short-term neuronal dynamics (STND) in the dorsal and ventral CA1 hippocampus under physiologically relevant conditions. Using extracellular recordings from hippocampal slices of male Wistar rats, we compared the effects of two CB1 receptor agonists, ACEA and WIN55,212-2, on network activity in the dorsal and ventral hippocampus. We found that both agonists significantly increased excitability and reduced PPI in the dorsal, but not the ventral, hippocampus. Similarly, CB1 receptor activation modulated STND more prominently in the dorsal hippocampus, reducing facilitation at low frequencies and reversing depression at high frequencies, whereas effects on the ventral region were minimal. These dorsoventral differences in the actions of cannabinoid receptor agonists occurred despite similar CB1 receptor expression levels in both regions, suggesting that functional differences arise from downstream mechanisms rather than receptor density. Pre-application of the GIRK channel blocker Tertiapin-Q occluded the effects of WIN55,212-2 on STND, indicating a significant role of GIRK channel-mediated signaling in CB1 receptor actions. These findings demonstrate that CB1 receptors modulate hippocampal circuitry in a region-specific manner, with the dorsal hippocampus being more sensitive to cannabinoid signaling, likely through differential engagement of intracellular signaling pathways such as GIRK channel activation. These results provide novel insights into how endocannabinoid signaling differentially regulates neuronal dynamics along the dorsoventral axis of the hippocampus. They also have important implications for understanding the role of cannabinoids in hippocampus-dependent behaviors.